Marathon training - For your personal best - Noakes, T.; Anderson, K.; Shepherd, J.; Brandon, R.; Hamilton, A.; Pedoe, D. T.; Tulloh, B. (Peak Performance, 2004)
Six-month training program: a comprehensive schedule for the non-specialist, tested in the lab and on the roads Beginner to elite performer: how a former couch potato applied training science to compete at the Commonwealth games Endurance training: the vital contribution of fast-twitch muscle fibres Warm-ups: why stretching doesn' t work. A new-style dynamic, sport-specific routine for runners Recovery: how to make recovery an integral part of your training success Hydration: could glycerol be the secret ingredient for hydration? Running risks: lies, damned lies and statistics: the truth about the incidence of injury, illness and death in marathon running Performance standards: the inexorable decline in Northern European endurance running Science section: Metabolic markers of peak performance · Injury risks for marathon 'virgins' · Carbohydrates and perceived exertion · Why distance running can be bad for bones · Why stiffer legs make running easier · Nature and nurture in Ethiopian endurance running success